The Influence of Transformational Leadership Style, Organizational Culture on Job Satisfaction and its Impact on Employee Performance at System Integrator Company PT. Aetherica Itanusa Persada in 2020 - Fare, Jumarni; Astuty, Pudji (Green Publisher Indonesia, 2024)
This study examines the factors related to Employee Performance at the system integrator PT Aetherica Itanusa Persada. The factors include Transformational Leadership Style, Organizational Culture, and Job Satisfaction, as independent variables, with Job Satisfaction functioning as an intervening variable that influences Employee Performance, treated as a dependent variable. The research was conducted over 5 months, from October 2019 to February 2020, including the design, implementation, and reporting of the research results. The population for this study consists of employees residing in DKI Jakarta. The sample for this research includes 97 employees of PT Aetherica Itanusa Persada, comprising 23 permanent employees and 74 non-permanent employees. The sampling technique used is purposive sampling, where samples are designated and selected by the researcher. The research results indicate that all hypotheses from the path analysis can be accepted, showing significant and positive effects. The R²m value is 0.759, meaning that 57.7% of the data variance can be explained by the model, indicating that the information contained in the data can be explained by 57.7%. The remaining 42.3% is explained by other variables outside the model. Several suggestions and recommendations can be made, including that leaders should pay attention to the intensity of meetings with their employees and conduct periodic training to achieve positive Employee Performance. Leaders and employees should maintain and implement the Organizational Culture effectively, adhere to established work regulations, and be consistent in their application.